Practical Aspects of Declarative Languages 8th International Symposium, PADL 2006, Charleston, SC, USA, January 9-10, 2006, Proceedings - van Hentenryck, Pascal (Programming and Software Engineering, 2006)
This volume contains the papers presented at the Eighth International S- posium on Practical Aspects of Declarative Languages (PADL 2006) held on January 9-10, 2006, in Charleston, South Carolina. Information about the c- ference can be found athttp://www.cs.brown.edu/people/pvh/PADL06.html. As is now traditional, PADL 2006 was co-located with the 33rd Annual Sym- sium on Principles of Programming Languages that was held on January 11-13, 2006. The PADL conference series is a forum for researchers and practioners to present original work emphasizing novel applications and implementation te- niques for all forms of declarative concepts. Topics of interest include, but are not limited to: - Innovative applications of declarative languages; - Declarative domain-speci?c languages and applications; - Practical applications of theoretical results; - New language developments and their impact on applications; - Evaluation of implementation techniques on practical applications; - Novel implementation techniques relevant to applications; - Novel uses of declarative languages in the classroom; - Practical experiences. This year, there were 36 submissions. Each submission was reviewed by at least three Programme Committee members. The committee decided to accept 15 papers. In addition, the programme also included three invited talks by Erik Meijer, David Roundy, and Philip Walder.